TINGKAT KEPUASAN PASIEN RAWAT JALAN TERHADAP PELAYANAN KEFARMASIAN DI DEPO FARMASI RAWAT JALAN RUMAH SAKIT ABDUL WAHAB SJAHRANIE SAMARINDA - Joshua Onesimus Brilian; Habel Roy Sulo; Maria Floriana Ping (Jurnal Farmasi Etam (JFE), 2024)
Pharmaceutical Services in Hospitals is a unit that cannot be separated from the entire service system in hospitals that focuses on patient care, the provision of pharmaceutical preparations, medical devices, and Medical Consumables (BMHP) that are affordable for every community, one of which is pharmaceutical services. clinic. Pharmaceutical services can be identified through the satisfaction level of outpatients. The purpose of this study was to determine the level of satisfaction of outpatients with pharmaceutical services at the Pharmacy Installation of Abdul Wahab Sjahranie Hospital, Samarinda. This study uses a questionnaire sheet which was carried out in July – August 2022. The sample used was outpatients who received services at the Pharmacy Installation of Abdul Wahab Sjahranie Hospital, Samarinda, which were taken by purposive sampling. Data analysis was carried out by calculating the percentage using the TKP formula. The results of the analysis of patient satisfaction levels obtained are very satisfied tangibles (89%), very satisfied reliability (86%), very satisfied responsiveness (84%), very satisfied assurance (85%) and very satisfied empathy (85%).